Veriown: Connecting the invisible woman in India - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2019)
This case is set in 2018, when Veriown, a pay-as-you-go Internet connected solar service provider, was preparing to launch in its first and potentially the most important market – India. Steve Johanns, the founder CEO of the company had pinned his hopes on the success of this launch to establish the viability of Veriown’s business model, its scalability within India, and expansion into sub-Saharan Africa. Established in 2016, Veriown’s primary objective was to bridge the infrastructural gap in energy that existed in developing countries by providing a safer and cleaner alternative to kerosene, a non-renewable fossil fuel that was detrimental to health and the environment. Besides energy, Veriown aimed to facilitate digital connectivity and access to financial services to help enable socio-economic development and financial inclusion of the impoverished rural communities. Empowered by a strong team, and supported by global partners, Veriown had developed an advanced solar energy-based solution that brought electricity, the Internet and micro-finance services together on the same platform, and followed the ‘pay-to-consume’ model of the kerosene transactions that consumers at the bottom of the pyramid (BoP) preferred. It had also tied up with local companies with expertise in distribution and installation of solar energy solutions in rural India for on-ground support during the launch. However, despite all the planning, Johanns was concerned about the operational capability of Veriown in meeting the high consumer demand of the market. He wondered if its service levels and frequency would be able to keep up with the demand, and effectively resolve any issues as and when they appeared. In addition, would the company be able to scale up soon after the launch, if required? Would leveraging its partners’ networks curtail the extent of control Veriown could wield over customer experience on the ground? This case will help students understand what it takes to be a social enterprise (SE), and learn to evaluate the potential of a SE by analysing not only its ability to create value, but also to localise it, meet the willingness to pay criteria of the poor, and win their trust. The students will be able to analyse the business model of a SE, develop an understanding of value chain, and learn about the significance of last mile distribution.